The goose girl - Hale, Shannon. frey50; Bishop, Cynthia; Findaway World; Full Cast Audio (Firm) (Chagrin Falls, Ohio : Findaway World ; [Syracuse, N.Y.] : Full Cast Audio, 2005)
Princess Anidori, on her way to marry a prince she has never met, is betrayed by her guards and her lady-in-waiting and must become a goose girl to survive until she can reveal her true identity. Dramatization.
"Playaway"--Container.
Issued on Playaway, a dedicated audio media player.
Originally released by Full Cast Audio in 2005.
Findaway World copyright date on container: 2006.
Read by Cynthia Bishop and the Full Cast family.
Keywords: Princesses; Human-animal communication; Fairy tales; Princesses; Human-animal communication; Children's audiobooks